Knowing isn't enough: Menstrual symptoms drive perceived performance impacts in women's football - Oester, C.; Lovell, R.; Pedlar, C.; Bruinvels, G.; Wilson, B.; Norris, D. (Journal of Science and Medicine in Sport, 2026)
Objectives To examine whether menstrual health literacy (MHL) is associated with Australian female footballers' negative perceptions of the menstrual cycle and contraceptive use on athletic performance and availability, and to assess the influence of symptom count on these perceptions.